Temporal Prepositions in Romanian and German: A Contrastive Perspective - Chira, Oxana (Didactica Danubiensis, 2026)
Objectives: The paper provides a novel integrated model that combines semantic, contrastive, cognitive, and diachronic perspectives to explain cross-linguistic asymmetries in temporal prepositions. Prior Work: The study builds on cognitive-semantic research on the metaphorical mapping of space onto time, as well as on contrastive and typological approaches that highlight cross-linguistic differences in prepositional systems and case government. Approach: The analysis combines qualitative contrastive linguistics with corpus-based illustration, drawing on lexicographic sources, academic texts, and didactic materials. Temporal prepositions are classified semantically and compared in systematic tables that reveal patterns of convergence and divergence. Results: Findings show that both languages encode similar temporal relations, yet German favors monolexical, case-governed prepositions, whereas Romanian relies more on analytic constructions. These asymmetries generate interpretive and translational challenges despite partial functional equivalence. Implications: The study provides a clearer framework for teaching German as a foreign language, improving translation practice, and refining contrastive grammatical description in academic settings. Value: The paper offers an integrated semantic, contrastive, and cognitive account of temporal prepositions, linking synchronic description with diachronic explanation in a novel comparative model.